Identifikasi Sikap: Ketertarikan Meluangkan Waktu Belajar Fisika, Normalitas Ilmuwan, Adopsi Sikap Ilmiah - Dodi Setiawan Putra; Muhammad Sofyan Zain; Cahyono Subiantoro (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to look at students' interest in spending time learning physics, how is the normality of scientists in students' perspectives, and the adoption of students' scientific attitudes in class. The methodology used is quantitative research with a descriptive survey research design. The results showed students were still hesitant to spend time learning physics, students were still hesitant to behave like scientists, and students were able to apply scientific attitudes in class.